Analysis of a Macroeconomic-Multifactor Model for stock marketspost financial crisis 2007 (I) - Palomino Selem, Carlos (2015)
In this first paper, we have the purpose of present the theorical fundamentalsand the macroeconomic multifactor modelderived from those; this model isbased on the Balance of Federal Reserve System, applied to explain national stock exchanges’ returns in the USA after financial crisis the 2007.We propose to work the model using different macroeconomic variables to the original model of The Arbitrage Pricing Theory of Chen-Ross-Roll, and we keep on Shanken’s proxy, the same that we permit to build a model using difference variables to the proposals at the original model.Of other side, the operational definitions of the variables used in our model, also, differ of established in the original model; in this, the variables are defined as risk premium, in our proposal they are defined as risk premium price.